Responses of the chloroplast glyoxalase system to high CO2 concentrations. Issue 12 (2nd December 2018) - Shimakawa, Ginga; Ifuku, Kentaro; Suzuki, Yuji; Makino, Amane; Ishizaki, Kimitsune; Fukayama, Hiroshi; Morita, Ryutaro; Sakamoto, Katsuhiko; Nishi, Akiko; Miyake, Chikahiro
ABSTRACT: Sugar metabolism pathways such as photosynthesis produce dicarbonyls, e.g. methylglyoxal (MG), which can cause cellular damage. The glyoxalase (GLX) system comprises two enzymes GLX1 and GLX2, and detoxifies MG; however, this system is poorly understood in the chloroplast, compared with the cytosol. In the present study, we determined GLX1 and GLX2 activities in spinach chloroplasts, which constituted 40% and 10%, respectively, of the total leaf glyoxalase activity. In Arabidopsis thaliana, five GFP-fusion GLXs were present in the chloroplasts. Under high CO2 concentrations, where increased photosynthesis promotes the MG production, GLX1 and GLX2 activities in A. thaliana increased and the expression of AtGLX1-2 and AtGLX2-5 was enhanced. On the basis of these findings and the phylogeny of GLX in oxygenic phototrophs, we propose that the GLX system scavenges MG produced in chloroplasts during photosynthesis. Graphical abstract: : The glyoxalase system scavenges methylglyoxal produced in chloroplasts during photosynthesis.